1997
DOI: 10.1038/sj.sc.3100411
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain/dysaesthesiae in spinal cord injury patients: results of a multicentre study

Abstract: The aim of the multicentre study* entitled`Description and Documentation of Painful States in Spinal Cord Injury Patients', in addition to the description and documentation of chronic pain and stressful dysaesthesiae in SCI patients, was the search for correlations between these symptoms and medical and psychosocial variables. To this end, the sample was selected to be as representative as possible. All patients referred for in-patient or out-patient treatment at the centres taking part were enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
161
6
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(190 citation statements)
references
References 8 publications
16
161
6
7
Order By: Relevance
“…Neuropathic pain thought to be due to damage to the spinal cord and presenting topographically in the dermatomes below the damaged segments has been variously called spinal cord pain, phantom pain, diffuse pain, central remote pain, deafferentation pain, below level central pain and SCI pain. 5,[10][11][12][13][14][15] Such a confusion of number and nature of pain subtypes, and terms used, obviously impedes communication between clinicians, researchers and others. The authors agreed that it would be worthwhile to create a consensus classification based on international input and state-of-the-art basic and clinical scholarship.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain thought to be due to damage to the spinal cord and presenting topographically in the dermatomes below the damaged segments has been variously called spinal cord pain, phantom pain, diffuse pain, central remote pain, deafferentation pain, below level central pain and SCI pain. 5,[10][11][12][13][14][15] Such a confusion of number and nature of pain subtypes, and terms used, obviously impedes communication between clinicians, researchers and others. The authors agreed that it would be worthwhile to create a consensus classification based on international input and state-of-the-art basic and clinical scholarship.…”
Section: Introductionmentioning
confidence: 99%
“…Pain in persons with SCI has been found to interfere with daily activities beyond the functional limitations related to the injury 47,52,60,69,70. A recent survey found that participants with SCI-related pain rated only a few pharmacological pain treatments as more than "somewhat" helpful 76.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Therefore, both sets of factors should be considered in the design of an integrated strategy to manage pain.…”
Section: Introductionmentioning
confidence: 99%